The Development of Web-Based Learning using Interactive Media for Science Learning on Levers in Human Body Topic - Astuti, Lia; Wihardi, Yaya; Rochintaniawati, Diana; Prima, Eka Cahya (Journal of Science Learning, 2020)
Integrated curriculum is a popular way to develop 21st-century skills, but most of the materials are written on the books separately. Furthermore, web-based learning is an online learning media that can be accessed using an internet connection anytime and anywhere. However, many educational websites do not apply the principles of effective learning. Besides, the traditional learning methods tend to be bored for the students. In order to solve this problem, this study designed a website education that uses interactive content to assist students in learning levers in the human body topic as one of the integrated science materials. The process of developing an educational website consists of three steps: (1) analysis, (2) design, (3) construction making. This research method used descriptive method, and the experts' judgment will evaluate it on content, language, and media/IT. The questionnaires used the technology acceptance model (TAM) and five-dimensional interactivity to investigate the readability of the subjects' perception responses. The research subject was three science teachers and 31 students on private Junior High School in Bandung. According to the result, generally, it has a good evaluation of each aspect. But, the website education needs a strong signal to access for not taking load time consumer.